Eu3+ luminescence from different sites in a scheelite-type cadmium molybdate red phosphor with vacancies. Issue 33 (7th September 2015) - Guzik, M.; Tomaszewicz, E.; Guyot, Y.; Legendziewicz, J.; Boulon, G.
<x xml:space="preserve">Abstract</x> Spectroscopy of Eu3+ ions in Cd1−3xEu2x□xMoO4, points out the three main non-equivalent symmetry sites very close to each other, due to the subtle differences in emission. Eu3+ ions in this almost ideal red light phosphor possess S4 point symmetry.